Abdominal Neuroendocrine Tumors (Updates in Surgery,, 2018)
This book aims to equip readers with a better understanding of neuroendocrine tumors of the abdomen and explains how to manage them optimally by making use of novel therapeutic options that represent major advances on previous treatments. The most recent advances in epidemiology, genetics, molecular biology, biomarkers, pathology, diagnostics, clinical assessment, medical therapy, and surgical treatment are presented. The information and data provided will stimulate readers to develop their personal opinions on significant issues and assist in decision making in individual patients during routine clinical practice. The book features a multidisciplinary approach and is designed to meet the needs of all physicians seeking comprehensive guidance from experts on the management of patients with neuroendocrine tumors. It will also be of value for researchers wishing to acquaint themselves with the state of the art in the field and emerging research avenues. Abdominal Neuroendocrine Tumors is published in Springer's highly successful Updates in Surgery series, which now comprises more than 20 titles.